Вплив забруднення на формування генеративної сфери деяких видів роду Penstemon Schmidel. в умовах промислового майданчика гірничо-збагачувального підприємства - Gryshko, V.M.; Mashtaler, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of study of ore mining and processing enterprise "North ore mining and processing combine" Ltd influencing on generic development of five species of Penstemon Schmidel. genus: P. arizonicus A. Heller, P. cobea (Nutt.) Grosswhite, P. digitalis Benth., P. laevigatus Soland, P. venustus Dougl are presented. Characteristics of flowers and souvetye the features of surface ultrastructure of antheriferous corns, their sizes and pollen viability are investigated.